DÎVÂN-I HİKMET’İN KÖKŞETAV NÜSHASINDA {-UbAn} EKİ - ABDULKADİR ÖZTÜRK (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2024)
Dîvân-ı Hikmet, the work of Sufi and poet Ahmet Yesevi, the founder of Turkish Sufi literature and a common value of the Turkish world, is an important treasure for Turkish language history and Turkish literature. Dîvân-ı Hikmet sheds light on the history of the Turkish language with the linguistic materials it contains and it is the first example of Turkish Sufi Literature in terms of content and style. While the environment of Sufism and Turkish culture spread from Turkestan to Anatolia with Yesevi successors, his legacy, Dîvân-ı Hikmet, continues to transfer this cultural accumulation to the generations of the Turkish world through ages. This work, which was the source of the birth of a literature in the field of Sufism, also guides the Turks who are honored with Islam. National consciousness, customs and traditions, heroic epics, etc. conveyed through the narratives of Dede Korkut and it had spread through oral tradition in Anatolia. The light of “Turkification and Islamization” that Hoca Ahmet Yesevî lit in Turkestan was conveyed to the hearts of followers and successors such as Hacı Bektaş-ı Veli, Yunus Emre, Abdal Musa, Baba Mansur, Haydar Sultan, Hubyar Sultan, who were his spiritual companions and heirs. This is how the permanence of Turkishness and Islam in Anatolia was realized. At the same time, there is the formation of a written Oghuz language in Anatolia by these important figures and other mystics, poets and literary figures. Oghuzs, who took their place on the stage of history since ancient times, lived in the 10th11th centuries. It is a Turkish tribe that spread to wide geographies over the centuries and left its mark on Turkish and Islamic history with the Seljuk and Ottoman states. The Oghuz people, who kept their language alive through oral tradition until the 13th century, created a new written language of the historical Turkish language in Anatolia. A new branch of written language, which we call the Western Turkish written language, and which differs from the Eastern Turkish written language, which has progressed in the direction of Kokturk, Old Uyghur, Karakhanid, Khwarezm and Chagatai Turkish, with its unique linguistic features, has emerged in this process. In this study, the gerund suffix {-UbAn} used in Dîvân-ı Hikmet, a work of the Eastern Turkish written language, will be discussed. In addition, the parallelism of this suffix with the texts of Old Oghuz Turkish, the first phase of the Western Turkish written language, will be evaluated.